Sorry, Not Sorry: Effects of Different Types of Apologies and Self-Monitoring on Non-verbal Behaviors - Yamamoto, Kyoko; Kimura, Masanori; Osaka, Miki (Frontiers in Psychology, 2021)
This study examines the effects of different types of apologies and individual differences in self-monitoring on nonverbal apology behaviors involving a server apologizing to a customer. Apologies divide into sincere apologies that reflect genuine recognition of fault, and instrumental apologies, made for achieving a personal goal such as avoiding punishment or rejection by others. Self-monitoring (public-performing and other-directedness) were also examined. Fifty-three female undergraduate students participated in the experiment. Participants were assigned randomly to either a sincere apology condition or an instrumental apology condition. They watched the film clip of the communication between a customer and server and then role-played how they would apologize if they were the server. Participants’ nonverbal behavior during the role-play was videotaped. The results showed an interaction between the apology condition and self-monitoring on nonverbal behaviors. When public-performing was low, gaze avoidance was more likely to occur with a sincere apology than an instrumental apology. There was no difference when the public-performing was high. Facial displays of apology were apparent in the instrumental apology compared to the sincere apology. This tendency became more conspicuous with increased public-performing. Our results indicated that the higher the public-performing, the more participants tried to convey the feeling of apology by combining a direct gaze and facial displays in an instrumental apology. On the other hand, results suggest that lower levels of public-performing elicited less immediacy in offering a sincere apology. Further studies are needed to determine whether these results apply to other conflict resolution situations.